Hakekat Filsafat Hukum dalam Pembangunan Hukum Nasional - Pratiwi, Ida Ayu Windhari Kusuma; Pitriyantini, Putu Eka; Suardana, I Wayan (Universitas Tabanan, 2022)
Law is a science, although law has its own characteristics because the object of study is quite broad. Legal science as a science also undergoes a process. As a science that is Sui Generis, it can be said that law has a fairly broad field of study consisting of three layers, namely; legal dogmatic layers, legal theory, and legal philosophy, and the three layers of legal science have benefits for the development of national law. This study has two problem formulations: What is the role of legal philosophy in the development of the national legal system and how is the implementation of legal philosophy in solving legal problems. The method used in this study is the normative legal methodology, which examines legal issues from the perspective of norms. The role of philosophy of law in the development of the national legal system is the basis for the level of abstraction of theoretical reflection whose level of abstractness is at the highest level and therefore permeates all forms of theoretical legal exploitation and practical legal exploitation. The implementation of legal philosophy in solving legal problems is to provide a basis for every legal decision which is used as a reference for decision makers to solve legal problems in order to achieve justice in society and legal certainty. An example is the event of a norm conflict between Article 24 A of the 1945 Constitution and Article 251 of Law Number 23 of 2014 concerning Regional Government